The North structure: evidence for a second possible impact event at the Bloody Creek site, Nova Scotia, Canada - Spooner, Ian; Pufahl, Peir; Brisco, Trevor; Morrow, Jared; Nalepa, Mariella; Williams, Peter; Stevens, George (Atlantic Geoscience, 2015)
The North structure is a discontinuous, partially flooded elliptical basin 250 m in diameter and defined by arcuate scarps. It is located in Annapolis County, Nova Scotia, approximately 1 km north of the Bloody Creek structure, a possible 400 m-diameter elliptical impact crater. Geophysical surveys indicate that raised scarps border a broadly elliptical basin with depth/diameter ratios similar to those at the Bloody Creek structure. Percussion coring and probing indicated that the basin is in-filled with 3.5 m of lacustrine sediment and peat overlying post-glacial alluvial sediment and diamicton. Samples collected proximal to the rim of the structure contain kink-bands in feldspar and biotite and possible planar microstructures in quartz and feldspar. The elliptical nature and similar, anomalous morphometries of the North and Bloody Creek structures indicate that two, low-angled, genetically linked impacts may have taken place at the site. Both structures are interpreted to be post-Pliocene (<2.6 Ma), based on the unlikelihood of their preservation during Cretaceous-Paleogene regional peneplanation.